2015
DOI: 10.1039/c5ra10332k
|View full text |Cite
|
Sign up to set email alerts
|

Unusual crystallization behavior of biodegradable poly(ethylene adipate) based nanocomposites induced by graphene oxide

Abstract: In the present research, we successfully prepared a series of graphene oxide (GO)/biodegradable poly(ethylene adipate) (PEA) nanocomposites through a simple solution and precipitation process. The scanning electron microscopy observation revealed a fine dispersion of GO with layered structure throughout the PEA matrix.The crystal structure, nonisothermal melt crystallization behavior, overall isothermal melt crystallization kinetics, spherulitic morphology, and spherulitic growth rate of the PEA/GO nanocomposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Banded spherulites were oen observed in some semicrystalline polymers, such as poly(ethylene adipate) (PEA), poly(butylene succinate) (PBS), poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBHHx), etc. [20][21][22] These polyesters usually formed featured banded spherulites in a certain range of T c and exhibited different spherulites morphology at other T c values. It should be noted that the origin of the banded spherulites is still an open and unsolved issue in polymer crystallization.…”
Section: Spherulitic Morphologies and Growth Kineticsmentioning
confidence: 99%
“…Banded spherulites were oen observed in some semicrystalline polymers, such as poly(ethylene adipate) (PEA), poly(butylene succinate) (PBS), poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBHHx), etc. [20][21][22] These polyesters usually formed featured banded spherulites in a certain range of T c and exhibited different spherulites morphology at other T c values. It should be noted that the origin of the banded spherulites is still an open and unsolved issue in polymer crystallization.…”
Section: Spherulitic Morphologies and Growth Kineticsmentioning
confidence: 99%
“…Poly(ethylene adipate) (PEA) is a biodegradable aliphatic polyester made from glycol and diacid. However, PEA shows a slower crystallization rate and poor thermal stability, which limits its application [7,8]. The crystalline properties of PEA can be enhanced by blending it with several nucleation agents [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…However, PEA shows a slower crystallization rate and poor thermal stability, which limits its application [7,8]. The crystalline properties of PEA can be enhanced by blending it with several nucleation agents [7,8]. It has been reported that graphene oxide (GO), as a nucleation agent, has good dispersion in a PEA/GO composite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 Therefore, extensive works have been done to incorporate graphene into various polymers and investigate the properties of the formed composites. [12][13][14][15][16] The dispersion state of graphene plays a vital role in the nal properties of the composites. Small addition could signicantly reinforce many properties of host polymers if in which graphene dispersed uniformly.…”
Section: Introductionmentioning
confidence: 99%